Difficulties face final year students at the Faculty of Education during their graduation projects from their point of view (AL-Mukhtar Journal of Educational Sciences, 2023)
The current study aims to identify the most important problems faced by final year students at the College of Education - Al-Bayda - at Omar Al-Mukhtar University while carrying out their graduation projects from their point of view during the second half of the year 2021/2022. The sample of the study consisted of (50) final year students at the College of Education - Al-Bayda - at Omar Al-Mukhtar University, who were deliberately selected. For the purpose of collecting data or information, it relied on the descriptive approach, and a questionnaire was applied in the study to the problems faced by the study sample during their graduation projects after verifying its validity. In order to analyze the results and then calculate the frequencies and averages, the study reached the following results:• The researcher finds that the study sample suffers from a high academic load in the eighth semester, which is the semester in which the graduation project is scheduled.• The study sample also suffers from a lack of experience in preparing a proposal for a graduation project plan, despite the presence of the research hall course for the seventh semester, but the training during which to prepare plans for graduation projects still requires more effort.
Keywords: Faculty of Education students; Graduation projects; Functional constructivism; Social construction; Social organization